ESBL E. coli Urosepsis Resulting in Endogenous Panophthalmitis Requiring Evisceration of the Eye in a Diabetic Patient - Tejaswini Arunachala Murthy; Pradeep Rangappa; Sangeetha Rao; Karthik Rao (Case Reports in Infectious Diseases)
A primary infection in a remote site resulting in vision threatening complications like panophthalmitis in a person who is not immune-compromised is rare. We report a case of endogenous bilateral bacterial endophthalmitis progressing into panophthalmitis in one eye requiring evisceration of that eye. A patient admitted with severe ESBL E. coli urosepsis was effectively treated with source control (bilateral DJ stenting for hydroureteronephrosis) and antibiotics. She was found to have features suggestive of bilateral conjunctivitis which progressed to panophthalmitis possibly due to delay in appropriate diagnosis and treatment. Diagnosis requires a very high index of suspicion if eye involvement is noted in a patient with features of bacteraemia and early intervention could possibly produce better outcomes. To our knowledge, this is the first case of ESBL E. coli urosepsis complicated by microbiologically confirmed panophthalmitis.